DESTAR MELAYU DARI PERSPEKTIF TERMINOLOGI: MALAY DESTAR FROM THE PERSPECTIVE OF TERMINOLOGY - Mohd Bukhari, Nur Azimah; Abdul Wahid, Puteri Roslina; Samsudin, Nurul Haniza (Jurnal Pengajian Melayu (JOMAS), 2020)
This paper discusses Malay couture from the perspective of terminology, based on the socioterminology approach to describe the use of specific terms in the community, namely the Malay headgear ‘destar’. Literary research on Malay couture has been done by researchers of the past and present. Couture is part of material culture that highlights the wisdom of Malay ceremonial traditions and worn by men and women. Despite showing blurred images, history books and ancient manuscripts could still be made points of references today. Malay couture was first mentioned in the 16th century as it developed from within the palaces of the Melaka sultanate during its prime in the Malay Archipelago. In this study, literary research was first conducted to collect a substantial corpus as a foundation for the concept of ‘destar’. This historiography was then used to support subsequent interviews with informants. The results and discussion focused on basic concepts of the ‘destar’. This is critical to providing a concrete explanation for the need to produce a Malay arts glossary that has been neglected thus far. The desire to explore Western technology has shrugged off the beauty of the Malay language that has been preserved in its couture, especially the ‘destar’. There is also a dire lack of effort to introduce Malay terminology at the international level due to the trend of assuming Western terminology are more sellable. Hence, this discussion on Malay couture terminology, specifically the ‘destar’, is expected to trigger more in-depth research towards making glossaries on the issue. Keywords: Malay culture, Malay couture, terminology, socioterminology, concept.